Efektifitas Perlindungan Hukum Pemegang Saham Dibawah 1/10 Dalam Mekanisme Pelaksanaan Gugatan Derivative Action - Imam Hakim Masyhuri; Wasiatun Wasiatun; Sumriyah Sumriyah (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
PT as a legal entity in carrying out legal actions must go through its management. Without a legal entity it will not work. The relationship between the directors and the company apart from being based on a working relationship, the directors also have a fiduciary relationship with the company. The Board of Directors has a fiduciary position in the company. Regarding the losses suffered by the company, both violations suffered by the company, whether violations of fiduciary obligations, ultra vires, or other mistakes committed by members of the board of directors, the shareholders of the company concerned have the right to file a derivative action (derivative action or derivative suit) against the members of the board of directors. Responsibility for the decision of the lawsuit is borne by the company. In addition, the obstacle that is often encountered in this case is that lawsuits that have been submitted to the court are often passive in handling them. An error or omission that results in a loss within the company, as the basis for a derivative lawsuit, has no clear criteria. This ambiguity results in it being difficult to qualify that the actions of the Directors or Commissioners have occurred by mistake or negligence, so shareholders can also take part in dealing with these problems when the company they run suffers losses caused by the Directors or Commissioners. The method used in this study is normative juridical with a case approach and statutory approach. So the purpose of our research is to find out how the legal protection of shareholders against companies is through Derivative Action lawsuits.